AB0793 Efficacy of IXEKIZUMAB improving SF-36 scores in biologic dmard-naive patients with active psoriatic arthritis: results from a phase 3 study (SPIRIT-P1). (15th June 2017) - Strand, V; Gottlieb, AB; Kvien, TK; Naegeli, A; Lin, C-Y; Benichou, O; Birt, J
Abstract : Background: In a phase 3 randomized controlled trial (RCT), ixekizumab (IXE), a high affinity mAb that selectively targets interleukin-17A, significantly improved signs and symptoms of psoriatic arthritis (PSA)and health status vs placebo (PBO) 1 . Objectives: To evaluate the efficacy of IXE improving patient (pt)-reported health status, assessed by Short Form Survey (SF-36) physical and mental component summary (PCS and MCS) and domain scores in pts with active PSA vs PBO, compared with age-and gender (A/G)-matched population normative scores 2 . Methods: In phase 3 RCT (SPIRIT-P1; NCT01695239 ), bDMARD-naive pts with active PSA (N=417) randomly received IXE 80 mg either once every 4 Wks (Q4W) or 2 Wks (Q2W) after a 160 mg starting dose, or 40 mg adalimumab (ADA) Q2W, or PBO (all subcutaneous). Health status was assessed by SF-36 at baseline, Wk 12, and Wk 24. Treatment comparisons were by mixed model for repeated measures for continuous data and logistic regression for categorical data. Missing values were imputed by nonresponder imputation. Results: Baseline SF-36 scores were similar across treatment groups. At Wk 24, significant improvements vs PBO were observed with ADA and IXEQ2W for PCS, and 5/8 domains (PF, RP, BP, GH, and RE), and with IXEQ4W for PCS and 6/8 domains (except VT and MH) (Figure) (post hoc for individual domains). In pts with baseline scores <A/G norms, significant improvements vs PBO were observed with ADA and IXEQ4W for PCS, MCS, and 5/8 domain scores (PF, RP, BP, VT and RE) and with IXE Q2W for PCS, MCS, and 7/8 domains (except MH) (post hoc). Within the same subgroup, a greater percentage of pts in each of the 3 active groups reported SF-36 scores ≥normative values at Wk 24 vs PBO, with statistical significance for PCS, MCS, and majority of the individual domains (Table) (post hoc). Conclusions: In pts with active PSA, both IXE and ADA treatment groups reported significant improvements in pt-reported health status as assessed by SF-36 and the majority of its individual domains, both in the general trial population, and in the subgroup of pts with baseline scores <A/G norms. References: Mease PJ et al. ARD, 2017, 76(1):79–87. Ware J, et al. How to score version 2 of the SF-36 health survey. Lincoln, RI: QualityMetric Inc.; 2000. Disclosure of Interest: V. Strand Consultant for: Eli Lilly and Company, Abbvie, Amgen, BMS, Boehringer Ingelheim, Celltrion Corrona, EMDSerono, GSK, Janssen, Merck, Novartis, Pfizer, Regeneron, Sandoz, Sanofi, UCB, A. Gottlieb Grant/research support from: Centocor (Janssen), Amgen, Abbott (Abbvie), Novartis, Celgene, Pfizer, Lilly, Levia, Merck, Xenoport, Dermira, Baxalta, Consultant for: Amgen Inc.; Astellas, Akros, Centocor (Janssen), Inc.; Celgene Corp., Bristol Myers Squibb Co., Beiersdorf, Inc., Abbott Labs. (Abbvie), TEVA, Actelion, UCB, Novo Nordisk, Novartis, Dermipsor Ltd., Incyte, Pfizer, Canfite, Lilly, Coronado, Vertex, Karyopharm, CSL Behring Biotherapies for Life, Glaxo Smith Kline, Xenoport, Catabasis, Meiji Seika Pharma Co., Ltd, Takeda, Mitsubishi, Tanabe Pharma Development America, Inc, Genentech, Baxalta, Kineta One, KPI Therapeutics, Crescendo Bioscience, Aclaris, Amicus, Reddy Labs, T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB, A. Naegeli Employee of: Eli Lilly and Company, C.-Y. Lin Employee of: Eli Lilly and Company, O. Benichou Employee of: Eli Lilly and Company, J. Birt Employee of: Eli Lilly and Company